Sounds in Melipona costaricensis (Apidae: Meliponini): effect of sugar concentration and nectar source distance - Aguilar Monge, Ingrid (2002)
The principal finding presented here is that Melipona costaricensis produces sounds that vary significantly in relation to varying sugar concentrations. Several components of the sounds produced, during the bees’stay inside of the hive,were positively correlatedwith sugar concentration: song duration, probability of sound production, duration of the long pulses and the relationship between short / long pulsed sound. Number of pulses per song was negatively correlated with sugar concentrations. The duration of all sound pulses was significantly correlatedwith the distance of the food source. Duration of the short pulses and interpulseswere significantly affected by the distance of the food source. Sounds may contribute to the recruitment of nestmates to increasingly rich food supplies during the day. It is clear that aspects of the sound signals are correlated with profitability of food sources.